2013
DOI: 10.1155/2013/926230
|View full text |Cite
|
Sign up to set email alerts
|

Detection ofMycobacterium tuberculosisby Using Loop-Mediated Isothermal Amplification Combined with a Lateral Flow Dipstick in Clinical Samples

Abstract: Tuberculosis (TB) is a communicable disease caused by the bacterium Mycobacterium tuberculosis (MTB) and is a persistent problem in the developing countries. Loop-mediated isothermal amplification (LAMP) allows DNA to be amplified rapidly at a constant temperature. Here, a LAMP method was combined with a chromatographic lateral-flow dipstick (LFD) to detect IS6110 gene of M. tuberculosis specifically and rapidly. The reaction was optimized at 63°C for 60 min, and the amplified DNA hybridized to an FITC-labeled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…To test for cross-hybridization using the AuNP probe with LAMP products from other pathogens, the amplicons from a VP AHPND DNA template (this study) served as the positive control for analysis by the AuNP colorimetric assay (analyzed by naked eye and confirmed by UV-vis spectrophotometry). The results were compared with those obtained using LAMP or RT-LAMP amplicons obtained by comparable LAMP methods for the following non-shrimp pathogens Mycobacterium tuberculosis (TB) [ 21 ] and Plasmodium (Malaria) [ 22 ], and for the shrimp pathogens WSSV [ 23 ], YHV [ 12 ], IMNV [ 13 ], IHHNV [ 24 ], TSV [ 25 ], LSNV [ 26 ] and PemoNPV [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…To test for cross-hybridization using the AuNP probe with LAMP products from other pathogens, the amplicons from a VP AHPND DNA template (this study) served as the positive control for analysis by the AuNP colorimetric assay (analyzed by naked eye and confirmed by UV-vis spectrophotometry). The results were compared with those obtained using LAMP or RT-LAMP amplicons obtained by comparable LAMP methods for the following non-shrimp pathogens Mycobacterium tuberculosis (TB) [ 21 ] and Plasmodium (Malaria) [ 22 ], and for the shrimp pathogens WSSV [ 23 ], YHV [ 12 ], IMNV [ 13 ], IHHNV [ 24 ], TSV [ 25 ], LSNV [ 26 ] and PemoNPV [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition to high sensitivity, the LAMP is also less prone to the presence of irrelevant DNA and inhibition compared to PCR and has the advantage of shorter reaction time, simple readout system and the use of cheaper technology tools [ 34 36 ]. As such, it enjoys increasing popularity for the diagnosis of a host of diseases [ 22 , 37 , 38 ]. Indeed, LAMP represents a powerful tool that can be employed in the evaluation of LF control activities, especially in the end-game when interruption of LF transmission must be certified.…”
Section: Discussionmentioning
confidence: 99%
“…Although these studies have revealed generally very good diagnostic performance, there are considerable discrepancies between their results891011121314151617181920212223242526272829303132. In addition, none of the studies could describe precise diagnostic accuracy because of their limited statistical power.…”
mentioning
confidence: 99%